2013
DOI: 10.1002/jmri.24017
|View full text |Cite
|
Sign up to set email alerts
|

Timing of the hepatic arterial phase at Gd‐EOB‐DTPA‐enhanced hepatic dynamic MRI: Comparison of the test‐injection and the fixed‐time delay method

Abstract: At EOB-enhanced hepatic dynamic MRI, the test-injection method yielded better image quality of hypervascular HCC and improved adequacy of timing of HAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Additionally, intravenous gadoxetic acid administration is frequently associated with acute transient dyspnea, which results in severe motion artifacts in 12.9–18% of arterial-phase gadoxetic acid-enhanced MR images (112728). These problems have been partially overcome by modification of contrast injection and imaging protocols, including a slower injection rate (1 mL/s rather than 2 mL/s) (2930), detection of arterial phase by test or fluoroscopic bolus monitoring rather than by fixed-scan delay (3132), and multiple short arterial-phase imaging (123334). However, acquisition of optimal arterial-phase gadoxetic acid-enhanced MR images is still challenging in clinical practice.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, intravenous gadoxetic acid administration is frequently associated with acute transient dyspnea, which results in severe motion artifacts in 12.9–18% of arterial-phase gadoxetic acid-enhanced MR images (112728). These problems have been partially overcome by modification of contrast injection and imaging protocols, including a slower injection rate (1 mL/s rather than 2 mL/s) (2930), detection of arterial phase by test or fluoroscopic bolus monitoring rather than by fixed-scan delay (3132), and multiple short arterial-phase imaging (123334). However, acquisition of optimal arterial-phase gadoxetic acid-enhanced MR images is still challenging in clinical practice.…”
Section: Methodsmentioning
confidence: 99%
“…A previous report suggested that optimal HAP timing was T test_peak + T full_bolus + T tumor − T k_space. 11 T test_peak was defined as the time to peak aortic enhancement from the start of test-bolus injection, T full_bolus as the time delay from peak aortic enhancement of the test bolus to peak aortic enhancement of the full bolus, T tumor as the time delay from peak aortic to peak tumor enhancement, and T k_space as the time to the center of the k-space acquisition. Previous report suggested that T full_bolus was equal to half of the contrast injection duration by evaluating the abdominal aorta of pig.…”
Section: Methodsmentioning
confidence: 99%
“…14 In addition, we have defined the T tumor as 8 seconds referenced with previous report. 11 Therefore, the optimal HAP was assumed to be T test_peak + T full_bolus + T tumor − T k_space = T test_peak + (half of the contrast injection duration) + 8 − T k_space. 11 Optimal HAP timing for the test-bolus protocol was also defined using the above equation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations